KEMAMPUAN SISWA SEKOLAH DASAR DALAM MERENCANAKAN DAN MENGEVALUASI PENYELIDIKAN ILMIAH PADA KONTEKS PENGARUH CAHAYA TERHADAP PERTUMBUHAN TANAMAN - Alfonsa Ina; Rusmawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to identify elementary school students’ ability to plan and evaluate scientific inquiry in the context of the effect of light on plant growth. The study employed a descriptive quantitative approach. The participants were fifth-grade elementary school students from a private school. Data were collected using a written multiple-choice test developed based on indicators of planning and evaluating scientific inquiry within the PISA 2025 framework. Data analysis was conducted using descriptive quantitative techniques by calculating scores and percentages of students’ achievement. The results showed that students’ ability to plan scientific inquiry was in the moderate category, with an average score of 74.86, while their ability to evaluate scientific inquiry was in the low category, with an average score of 64.00. Students were generally able to identify phenomena and investigation objectives; however, they experienced difficulties in identifying variables, formulating hypotheses, designing systematic procedures, and evaluating the appropriateness of procedures and data reliability. These findings indicate that elementary school students’ abilities to plan and evaluate scientific inquiry have not yet developed optimally. Therefore, science learning should emphasize inquiry-based approaches that explicitly train scientific inquiry skills in accordance with the PISA 2025 framework.